Modelling of Natural Convective Heating of a Standard Wet Brick for Oven Energy Consumption Tests. (August 2020) - Lucchi, M.; Suzzi, N.; Lorenzini, M.
Abstract: The environmental impact of buildings is directly influenced by low-efficiency appliances like electric ovens. Their energy class is estimated through a test prescribed by the EN 60350 European standard, where a wet clay brick is heated under set conditions and the energy consumption is measured; throughout the test, particular attention is devoted to the control of air temperature. In this work, a transient model of the oven suitable for control design was realized including the heat and mass transfer within the brick. A lumped-parameter approach was used to ensure good predictive properties and low computational cost. The dynamics of the cavity air and the Pt500, which is used in normal operation to maintain the desired set point, was also included in the model. Model parameters were determined through an optimization procedure based on the experimental data collected during energy consumption tests with the oven in natural convective heating mode. The model was then validated. Good results were obtained in the prediction of both temperature and heating time.